A novel fluorescent assay for the ultrasensitive detection of miRNA-21 with the use of G-quadruplex structures as an immobilization material for a signal indicator. Issue 45 (17th May 2019) - Yang, Ze-Zhou; Wen, Zhi-Bin; Peng, Xin; Chai, Ya-Qin; Liang, Wen-Bin; Yuan, Ruo
Abstract : A fluorescent assay for the ultrasensitive detection of miRNA-21 is based on immobilization of PPIX as signal indicators in massive G-quadruplex structures obtained by target recycling, three-dimensional DNA walker and RCA coupled cascade nucleic acid amplification. Abstract : In this work, a novel fluorescent assay was proposed for the ultrasensitive detection of microRNA-21 (miRNA-21) based on the efficient immobilization of protoporphyrin IX (PPIX) as signal indicators in massive G-quadruplex structures obtained by target recycling, three-dimensional DNA walker and a rolling circle amplification (RCA) coupled cascade nucleic acid amplification strategy.